Quality of Biology Laboratory SMA Muhammadiyah 1 Simo Boyolali Academic Year 2023/2024 - Khairunnisa, Luthfiyah; Setyaningsih, Endang (Universitas Muhammadiyah Surakarta, 2024)
The laboratory is one of the facilities available at school as a support for learning biology. The fulfillment of facilities and infrastructure in the biology laboratory will affect the success of learning. Biology learning does not only include theory but also direct practical activities. Therefore, to support the success of practicum-based learning, a biology laboratory must have adequate facilities and infrastructure by the minimum standards listed in Permendiknas Number 24 of 2007. This research aims to determine the quality of the biology laboratory at SMA Muhammadiyah 1 Simo Boyolali in the academic year 2023/2024. This research uses a qualitative descriptive method with data collection techniques in the form of observation and interviews. The results of this study indicate that the quality of the laboratory at SMA Muhammadiyah 1 Simo Boyolali has good criteria with a percentage of 78,31%, where these results are still lacking in meeting the minimum standards listed in Permendiknas Number 24 of 2007. This research concludes that the quality of the biology laboratory is classified as good even though it has not met the minimum standards by Permendiknas Number 24 of 2007.